Simplex PCR assay for detection of cow milk presence in goat milk - hazra, tanmay; sharma, vivek (Indian Journal of Dairy Science, 2016)
Goat is considered as poor man’s cow. Goat milk has many therapeutic properties. It is devoid of the problem like cow milk protein allergy. Demand of goat milk is increasing day by day due to its high therapeutic value, but at the same time the fact is that yield of goat milk is very low as compared to cow or buffalo milk. This demand and supply gap is responsible for the adulteration of goat milk with cow milk. Till date no rapid analytic technique is available to check the cow milk adulteration with goat milk. Therefore in the present study a simplex PCR based approach has been developed to detect cow milk adulteration in goat milk. A set of bovine specific primers (P1) targeting d-loop of mt-DNA (mitochondrial DNA) was selected and standardized to amplify cow DNA resulting into 126bp amplicon. Specificity of the primer was tested in goat and cow genomic DNA isolated from both milk and blood samples. Using this PCR based approach even upto 1% level of cow milk adulteration in goat milk could be detected. Designed protocol was quick and efficient enough to ascertain the adulteration of cow milk in goat milk.